1999
DOI: 10.1890/0012-9658(1999)080[0161:cboabb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Balance of a Boreal Bog During a Year With an Exceptionally Dry Summer

Abstract: Northern peatlands are important terrestrial carbon stores, and they show large spatial and temporal variation in the atmospheric exchange of CO 2 and CH 4 . Thus, annual carbon balance must be studied in detail in order to predict the climatic responses of these ecosystems. Closed-chamber methods were used to study CO 2 and CH 4 in hollow, Sphagnum angustifolium lawn, S. fuscum lawn, and hummock microsites within an ombrotrophic S. fuscum bog. Micrometeorological tower measurements were used as a reference fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
142
5
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(159 citation statements)
references
References 41 publications
11
142
5
1
Order By: Relevance
“…However, this carbon storage pool is threatened as many natural peatlands that are disturbed by human interference, for example, by peat cutting and land use change for agricultural use (Alm et al, 1999a;Drösler et al, 2008). In addition, the carbon storage potential of peatlands is threatened by climate-change-induced drought, as lower water tables lead to marked carbon emissions in peatland ecosystems (e.g., Alm et al, 1999b;Arneth et al, 2002;Aurela et al, 2007).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…However, this carbon storage pool is threatened as many natural peatlands that are disturbed by human interference, for example, by peat cutting and land use change for agricultural use (Alm et al, 1999a;Drösler et al, 2008). In addition, the carbon storage potential of peatlands is threatened by climate-change-induced drought, as lower water tables lead to marked carbon emissions in peatland ecosystems (e.g., Alm et al, 1999b;Arneth et al, 2002;Aurela et al, 2007).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…30% of the total soil carbon (Gorham 1991). The mire carbon balance reacts sensitively to variations in climate; therefore, interannual variation (Alm et al 1999) or a directional change in climate (Oechel et al 1995) can turn northern mires from carbon sinks into carbon sources. This, in turn, would have important feedback effects on the current climate change.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, would have important feedback effects on the current climate change. Especially peat moisture content and water table level are important controls of mire carbon exchange (Shurpali et al 1995;Alm et al 1999;Riutta et al 2007b). The timing of snow and surface frost melt have been observed to have an important influence on the annual carbon budget of northern mires (Aurela et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Updegraff et al (1995) have suggested that changes in nitrogen supply could cause shifts in carbon storage. Furthermore, both Griffs et al (2000) and Alm et al (1999) show that a peatland can become a net source during dry or drought years. All these changes are due to temperature increase and water table variation, but DOC increase has been shown to be more than 5 times higher than would be expected by temperature alone (Worrall et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%